Long-term Electricity Forecasting: A System Dynamics Approach - Ahmad, Salman; Razman, Mat Tahar (2012)
Electricity has become an important source of energy for human development. Forecasting electricity demand plays a pivotal role in electricity planning. It provides a mechanism to have a balance between supply and demand. A system dynamics model is developed using population and per capita consumption of electricity to forecast electricity demand for coming 10 years. Malaysia is used as a case study. It is found that that by using two variables, a fairly accurate forecast can be obtained. The simulation model estimates that at the current rate of consumption and population growth there will be a need of 192.5trillionwatt-hour of electric energy in year 2021.